Integrative Oncology: An International Perspective from Six Countries. (March 2021) - Toledano, Alain; Rao, Santosh; Frenkel, Moshe; Rossi, Elio; Bagot, Jean-Lionel; Theunissen, Ingrid; Díaz-Sáez, Gualberto
In June 2019, a meeting was held in Paris in which experts from different countries (Israel, Spain, Belgium, Italy, USA, and France) met to discuss a selection of topics in integrative oncology (IO). The objectives were to draw on the delegates' experience and expertise to begin an international collaboration, sharing details of differing existing models and discussing future perspectives to help define and guide practice in IO and define unmet needs. This report presents a summary of the meeting's main presentations, and also reports on the experts' responses to a questionnaire examining different aspects of IO service delivery, infrastructure, and utilization.